Prevalence of Multidrug Resistant Escherichia Coli in Pigeon in Mymensingh, Bangladesh (Microbes and Health, 2014)
To determine prevalence of antimicrobial resistant Escherichia coli in pigeon a total of 112 samples such as cloacal swabs (n=36), foot pads (n=36) and feces (n=40) were collected from pigeon aseptically. Samples were enriched in nutrient broth and then streaked onto eosine methylene blue agar, Salmonella-Shigella agar, MacConkey agar and blood agar. The cultural and biochemical characteristics of bacterial isolates of pigeon were indicative of E. coli. The prevalence of E. coli in cloacal swabs, foot pads and feces samples were 86.11%, 44.44% and 77.50%, respectively. The overall prevalence of E. coli in pigeon was 69.64% (78 of 122 samples were found positive for E. coli). The antibiotic sensitivity pattern showed that E. coli isolates were sensitive to erythromycin, ciprofloxacin, kanamycin, nalidixic acid and resistant to amoxicillin, tetracycline and sulphamethaxazole. It may be concluded that pigeons from Mymensingh locality in Bangladesh carry multidrug resistant E. coli. Data of this study will be helpful in creating public health awareness among people and help controlling transmission of drug resistant E. coli by undertaking effective sanitary and hygienic measures. Microbes and Health, June 2013, 2(1): 5-7DOI: http://dx.doi.org/10.3329/mh.v2i1.17254